Incidence of second primary cancers in oral and pharyngeal cancer patients using a large medical claims database in Japan - Masanori Matsui; Kahori Kawamura; Keita Kano; Hideki Yoshimatsu; Takashi Doi; Tatsuro Miyake (Elsevier, 2023)
Background/purpose: As the occurrence of second primary cancers (SPCs) is strongly related to the survival rate of patients with oral and pharyngeal cancers, early detection and treatment are important. Therefore, this study aimed to clarify the incidence of SPCs and their risk factors in patients with oral and pharyngeal cancer. Materials and methods: This observational study was conducted using data from the administrative claims database of 21,736 participants with oral and pharyngeal cancer from January 2005 to December 2020. We evaluated the cumulative incidence of SPCs among patients with oral and pharyngeal cancers using the Kaplan-Meier method. The Cox proportional-hazard model was used for multivariate analysis. Results: Of the 1633 patients with oral and pharyngeal cancer who qualified for analysis, 388 developed SPCs (incidence rate, 7.994/1000 person-months). The multivariate analysis showed that the risk of developing SPCs was affected by age at diagnosis of oral and pharyngeal cancer, cancer treatment, and anatomical site of the primary cancer. Conclusion: Patients with oral and pharyngeal cancers are at a high risk of developing SPCs. The data from this study may be useful in providing accurate information to patients with oral and oropharyngeal cancer.